Antiinflammatory Activity Patch Ethanol Extract Of Leaf Katuk (Sauropus Androgynus L. Merr) - Rise Desnita; Sri Luliana; Desy Siska Anastasia (Fakultas Farmasi Universitas Pancasila, 2018)
The leaf katuk (Sauropus androgynus L. Merr) extract at a dose of 400 mg / kg BW had antiinflammatory activity in rat by induction of carrageenan. Patch are adhesive plasters containing medicinal substances placed on the skin to delivery active substances. Patch can offer practicality, comfort and accuracy of dosage in the application of leaf S. androgynus extract.This research was a laboratory experimental research by making patch of leaf S. androgynus extract and inflammation effect used rats as its animal test. Inflammatory healing activity was seen from the percentage reduction in inflammation in rats after patch application. Patch of leaf S. androgynus extract dose 400 mg / kg BW has percentage of inflammatory inhibition ranged between 66,67-100%. Statistical test results using one-way anova patch leaf S. androgynus extract showed good effectiveness in curing inflammation. Effectiveness between leaf S. androgynus extract patch and diclofenac sodium patch relatively the same in curing inflammation.